Analysis of Conical Horn Antenna Radiation over Ground by Directional Currents Method - Polat, Burak; Dasbasi, Ramazan (IEEE, 2021)
Directional Currents Method, which was developed and tested for rectangular horn antennas recently by Polat and Dasbasi, is applied to derive explicit radiation fields of a conical horn antenna located over a simple lossy dielectric half-space. The influence of presence of transmission medium on E- and H-plane radiation performances of the conical horn is displayed under dominant mode excitation in comparison with similar results for a pyramidal horn in X-band. The accuracy of the radiation fields when the conical horn is located close to air-ocean interface is checked by comparing with the full wave simulation data of the commercial software CST (TM).
Keywords: conical horn antennas; Hertzian dipoles; radiowave propagation; Sommerfeld problem; surface waves; WAVES; Engineering; Telecommunications